Indications and techniques of percutaneous procedures Coronary, peripheral, and structural heart disease - Bavry, Anthony A.; Kumbhani, Dharam J.; SpringerLink (Online service) (Tarporley : Springer Healthcare Ltd., 2012)
Percutaneous and coronary interventions, used to treat narrow arteries of the heart caused by/found in those with coronary heart disease. This book is a detailed guide for performing percutaneous procedures and it covers in-depth the procedures that cardiologists and interested specialists must be aware of in order to use the devices proficiently
1 Vascular anatomy -- 2 Catheters, guidewires, sheaths, and balloons -- 3 Complex coronary interventions -- 4 Fractional flow reserve and intravascular ultrasound -- 5 Peripheral interventions -- 6 Structural heart disease.
Keywords: Medicine; Chemistry; Pharmacy; Literacy; Medicine & Public Health; Medicine/Public Health, general; Literacy; Biomedicine general; Pharmacy; Chemistry/Food Science, general